The relationship of exclusive breastfeeding with the return of menstrual time in mothers who have babies aged 6 -12 months in the work area of Pekik Nyaring Puskesmas, Bengkulu Central District - Sri Yanniarti; Veby Yunita Putri Omi; Rolita Efriani (Alma Ata University Press, 2023)
Background: Exclusive breastfeeding means giving only breast milk to babies from 30 minutes after birth (after birth) until the age of 6 months, without additional fluids, such as formula milk, fruit juices, water, honey, tea water and solid complementary foods such as fruit, biscuits, milk porridge. , rice porridge and team rice. Mothers who breastfeed exclusively, in principle, will get menstruation longer than those who do not exclusively breastfeed their babies. Objectives: The purpose of this study was to determine the relationship between exclusive breastfeeding and the duration of the return of menstruation in mothers who have babies aged 6-12 months in the Working Area of Pekik Nyaring Health Center, Central Bengkulu Regency. Methods: This research was conducted in December 2021 in the working area of the Pekik Nyaring Health Center, Central Bengkulu Regency using a kohort retrospektif.design. Determination of the number of samples using the slovin formula. The sample in this study were mothers who had babies aged 6-12 months in the Pekik Nyaring Health Center Work Area, Central Bengkulu Regency as many as 54 people spread over 7 villages with proportional random sampling technique. Results: The results showed that most of the respondents were under 35 years old with the most education level graduating from high school and most of them working as housewives. Most mothers who have babies aged 6-12 months give exclusive breastfeeding and get menstruation back more than six months. There is a significant relationship between exclusive breastfeeding and the length of return of menstruation for mothers who have babies 6-12 months in the Working Area of Pekik Nyaring Health Center, Central Bengkulu Regency.Conclusions: There is a significant relationship between exclusive breastfeeding and the duration of the return of menstruation in mothers who have babies 6-12 months in the Working Area of Pekik Nyaring Health Center, Central Bengkulu Regency